DNA Barcoding: An Efficient Tool to Overcome Authentication (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
The rapid expansion of the global herbal medicine market has intensified concerns regarding the authenticity, quality, and safety of medicinal plant–based products. Adulteration, substitution, and misidentification of herbal raw materials are common problems that compromise therapeutic efficacy, pose health risks, and reduce consumer confidence. Conventional identification methods based on morphological, microscopic, and phytochemical analyses are often inadequate, particularly for processed herbal products such as powders, extracts, and capsules, where diagnostic characteristics are lost. In this context, DNA barcoding has emerged as a reliable and scientifically robust molecular tool for accurate species identification. This review provides a comprehensive overview of the principles, methodology, commonly used barcode regions (rbcL, matK, ITS, and trnH-psbA), and applications of DNA barcoding in the herbal industry. The role of DNA barcoding in authentication, quality control, detection of adulterants, conservation of endangered medicinal plants, and regulatory compliance is discussed. Recent advancements, including DNA metabarcoding, mini-barcodes, next-generation sequencing technologies, and the integration of bioinformatics and artificial intelligence, have significantly enhanced its applicability, particularly for complex and highly processed herbal formulations. Although challenges such as DNA degradation and incomplete reference databases remain, ongoing improvements and global standardization efforts continue to strengthen the utility of DNA barcoding. Overall, this review highlights DNA barcoding as a powerful tool for ensuring the safety, authenticity, and sustainability of herbal medicines in the modern pharmaceutical and nutraceutical markets.
Keywords: DNA barcoding; Herbal medicine authentication; Medicinal plants; Adulteration detection; Quality control; DNA metabarcoding; Herbal industry